An improved MALDI‐TOF mass spectrometry procedure and a novel DNA marker for identifying over‐expressed Bx7 glutenin protein subunit in wheat. Issue 6 (December 2014) - Wang, Ke; Islam, Shahidul; Ma, Junhong; Anwar, Masood; Chen, Jing; Yan, Yueming; Appels, Rudi; Ma, Wujun
<x xml:space="preserve">Abstract</x> Wheat bread‐making quality is mainly determined by glutenin proteins in the grain, which exist in a wide range of variable alleles with differential influence on processing attributes. A recently identified allele, Bx7 over‐expression (Bx7oe), has been showing highly significant positive effects on wheat dough strength over the normally expressed Bx7 allele. SDS‐PAGE and normal RP‐HPLC procedures failed to separate the two alleles. In the current study, an extensively optimised MALDI‐TOF based procedure and a refined DNA based marker for efficiently differentiating Bx7oe from normal Bx7 allele were established. Results indicated that the MALDI‐TOF procedure is cost effective, high throughput, and proven reliable, while the refined PCR marker only amplifies Bx7oe allele, a clear advantage over the previously developed codominant marker.